The scientific knowledges lead the didactic approach - Capra, Luca; Lovecchio, Nicola (Formazione & insegnamento, 2019)
Outdoor game has many benefits on the integral development of the children and the individual. Considering the pedagogical analysis of the game; its importance was explained with a special focus on the thermoregulation process. The physiological phenomenon was, then, analyzed to lead some reflections and considerations to support outdoor game. The actual considerations about the outdoor practice according to scientific evidence could support new educational perspective. In this way children could improve the time spent in nature context since they suffer of a new disorder called Nature-Deficit.